Dynamics of Integrated Social Studies Learning Implementation in Junior High Schools: Case Study at SMPN 41 Medan - Wardani, Aulia; Efranita Purba, Desi Marcelina; Batubara, Rina Mawardah; Sugiharto, Sugiharto; Lubis, Darwin Parlaungan; Novira, Nina; Permana, Sendi; Vanda, Vanda (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2024)
Integrated social studies learning is a form of integrative learning applied in junior high schools by integrating several disciplines into one subject, namely geography, economics, sociology, and history. This provides obstacles for teachers teaching integrated social studies learning. The study aimed to determine the teachers' constraints and students' understanding of integrated social studies learning at SMPN 41 Medan. The research method used is a descriptive qualitative method. The study results explain that the teacher's constraints in integrated social studies learning include difficulty understanding learning material outside the science teacher's field, limited time allocation, lack of learning facilities and infrastructure, and differences in each student's characteristics. Student understanding in terms of Integrated IPS learning is very high. This can be seen from students' interest during the learning process. It attracts students' attention with a percentage of 87.5% so that the majority of students in this situation feel the learning process is enjoyable and is considered a positive indication that teaching methods and strategies the learning used by the teacher has succeeded in attracting student interest so that they can understand the Integrated Social Sciences learning material. Students' understanding of social studies learning can be a benchmark for teacher success in integrating several disciplines into one subject.